2021
DOI: 10.1016/s2214-109x(20)30470-8
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence, risk factors, prognosis, and health-related quality of life after stroke in a low-resource community in Chile (ÑANDU): a prospective population-based study

Abstract: Background Stroke is a leading cause of disability and death worldwide. The best estimates of local, national, and global burden of stroke are derived from prospective population-based studies. We aimed to investigate the incidence, risk factors, long-term prognosis, care, and quality of life after stroke in the Ñuble region of Chile. MethodsWe did a prospective community-based study with use of multiple overlapping sources of hospitalised, ambulatory, and deceased cases. Standardised diagnostic criteria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 46 publications
(57 reference statements)
6
65
1
5
Order By: Relevance
“…There was no significant difference in AF according to sex in patients aged 75 years and above [ 22 ]. A study in Chile showed that the frequency of AF in patients with ischemic stroke was similar to previous findings [ 23 ]; however, AF was more associated with females in another study conducted in China [ 12 ]. AF is also the most frequent risk factor for ischemic stroke among people with multiple vascular risk factors [ 10 ].…”
Section: Discussionsupporting
confidence: 81%
“…There was no significant difference in AF according to sex in patients aged 75 years and above [ 22 ]. A study in Chile showed that the frequency of AF in patients with ischemic stroke was similar to previous findings [ 23 ]; however, AF was more associated with females in another study conducted in China [ 12 ]. AF is also the most frequent risk factor for ischemic stroke among people with multiple vascular risk factors [ 10 ].…”
Section: Discussionsupporting
confidence: 81%
“…Por otra parte, en un estudio ejecutado en la Región de Ñuble (2021) la incidencia de ECV ajustada por edad fue 163,4 por 100.000 habitantes. La letalidad a 30 días fue de 24,6% y de 30% a los 6 meses 9 .…”
Section: Discussionunclassified
“…Although abundant evidence has shown stroke led to lower quality of life [ 8 , 15 17 ], few studies have explored the opposite direction–-the impact of quality of life on stroke. Using stroke risk as dependent variable, and quality of life and its four domains as dependent variables, our study has consistently shown that lower quality of life (including lower physical health, psychological health, social relationships, and environment) was associated with higher risk of stroke in multinominal logistic regressions.…”
Section: Discussionmentioning
confidence: 99%
“…The association between psychosocial factors such as quality of life and stroke risk has also been widely studied, with most studies showing that people’s quality of life significantly decreased after stroke [ 8 , 15 17 ]. Although quality of life has been frequently assessed as a poststroke outcome, evidence has shown that quality of life also serves as an important predictor for some major diseases such as myocardial infarction (MI), heart failure, diabetes mellitus, and hemodialysis [ 18 23 ].…”
Section: Introductionmentioning
confidence: 99%